A METHOD OF INTEGRATED ASSESSMENT OF LIVER FIBROSIS DEGREE: A COMPARISON OF THE OPTICAL METHOD FOR THE STUDY OF RED BLOOD CELLS AND INDIRECT ELASTOGRAPHY OF THE LIVER - M. V. Kruchinina; S. A. Kurilovich; A. A. Gromov; V. M. Generalov; A. S. Safatov; G. A. Buryk; G. V. Shuvalov (SINAPS LLC, 2017)
The presented  method  of integrated  assessment of liver fibrosis degree based on the comparison of the data obtained in the study of electric and viscoelastic parameters of erythrocytes by the dielectrophoresis  method  using the electro-optical system  of the detection  cells and method  for indirect elastometry. A high degree of comparability of the results of the above-described  methods  was established  when the degree of fibrosis F 2-4  in the  absence  of marked  cytolysis, cholestasis,  inflammatory  syndrome,  metal  overload. It is shown that  parallel using the methods  of dielectrophoresis and indirect elastography is needed in the presence of a rise of transaminases, gammaglutamyltranspeptidase more than 5 norms, expressed dysproteinemia,  syndromes of iron overload, copper to increase the accuracy in determining the degree of liver fibrosis. The evaluation of dynamics of changes of the degree of fibrosis during antiviral therapy is more accurate by the method  of indirect elastometry, and the method of dielectrophoresis  is preferable in the treatment of nonalcoholic fatty liver disease. In cases of restrictions on the use of the method  for indirect elastography (marked obesity, ascites, cholelithiasis, pregnancy, presence of pacemaker, prosthesis) to determine  the degree of fibrosis the method of dielectrophoresis  of red blood cells can be used. Simultaneous use of both methods  (using the identified discriminatory values) allows to reduce or to neutralize their disadvantages, dependence on associated syndromes, to expand the possibilities of their application, to improve the diagnostic accuracy in determining each of the degrees of liver fibrosis. Integrated application of both methods - indirect elastography and dielectrophoresis of red blood cells - for determining the degree of liver fibrosis allows to achieve high levels of sensitivity (88.9 percent) and specificity (100 percent) compared to the "gold standard" - biopsy of the liver.